Therapeutic Advances in Oncology - Liu, Jinsha (Int J Mol Sci, 2021)
Around 77 new oncology drugs were approved by the FDA in the past five years; however, most cancers remain untreated. Small molecules and antibodies are dominant therapeutic modalities in oncology. Antibody-drug conjugates, bispecific antibodies, peptides, cell, and gene-therapies are emerging to address the unmet patient need. Advancement in the discovery and development platforms, identification of novel targets, and emergence of new technologies have greatly expanded the treatment options for patients. Here, we provide an overview of various therapeutic modalities and the current treatment options in oncology, and an in-depth discussion of the therapeutics in the preclinical stage for the treatment of breast cancer, lung cancer, and multiple myeloma.